2001
DOI: 10.1029/2000jd900752
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry‐transport model comparison with ozone observations in the midlatitude lowermost stratosphere

Abstract: Abstract.About 600 ozone sonde profiles and in situ ozone observations on 2300 aircraft flights were compared with several three-dimensional global chemistrytransport models, in the midlatitude lowermost stratosphere during 1996. The models use the same top boundary conditions and parameterized ozone chemistry.The comparisons show that the models using general circulation model (GCM) winds do not capture the seasonal ozone accumulation in the lowermost stratosphere. The models using winds from the European Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…Primary production of OH radicals in the UT/LS region depends not only on O 3 and H 2 O levels but also on carbonyls and peroxides whose concentrations are again strongly linked to vertical transport and mixing (Jaeglé et al, 2001;Brühl et al, 2000;Prather and Jacob, 1997). Finally, due to the relatively long lifetimes and steep vertical gradients of many compounds in the UT/LS region small inaccuracies in the advection scheme may significantly affect their concentration levels (Bregman et al, 2001). The downward flux of ozone from the stratosphere to the troposphere is particularly sensitive to the formulation of transport and to upper (stratospheric) boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary production of OH radicals in the UT/LS region depends not only on O 3 and H 2 O levels but also on carbonyls and peroxides whose concentrations are again strongly linked to vertical transport and mixing (Jaeglé et al, 2001;Brühl et al, 2000;Prather and Jacob, 1997). Finally, due to the relatively long lifetimes and steep vertical gradients of many compounds in the UT/LS region small inaccuracies in the advection scheme may significantly affect their concentration levels (Bregman et al, 2001). The downward flux of ozone from the stratosphere to the troposphere is particularly sensitive to the formulation of transport and to upper (stratospheric) boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The models involved in TRADEOFF have contributed to numerous previous studies on the impact of aircraft emissions (Penner et al, 1999;Brasseur et al, 1998;Grewe et al, 2001;Meijer et al, 2000;Rogers et al, 2000;Pitari and Mancini, 2001) and participated in previous evaluation studies (Bregman et al, 2001;Law et al, 2000;Rogers et al, 2000;Penner et al, 1999;Brasseur et al, 1998;Houghton et al, 2001). Recently, Law et al (2000) compared monthly mean ozone fields of five CTMs with data from the MOZAIC program, in which ozone is measured continuously from passenger aircraft (Marenco et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The models generally showed good agreement with observations but often failed to capture sharp ozone concentration gradients in the tropopause region and between extra-tropical and tropical regions. A third intercomparison of ozone models focused on the seasonality of LS ozone and the role of vertical transport [Bregman et al, 2001]. It was found that chemistry-transport models may simulate highly different vertical transport efficiencies in the LS, even when they apply meteorological data from the same source to calculate advection, e.g., from ECMWF analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spatial gradients are small in the UT/LS, which complicate the model evaluation. To overcome this problem, model evaluations were performed with short-lived species (e.g., CO,O 3 , NO x , OH, 14 CO,222 Rn/ 210 PB), which show much stronger spatial gradients [Bregman et al, 2001;Jöckel et al, 2002;Rotman et al, 2004;Brunner et al, 2003Brunner et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%